Industrial development in East Africa - Pearson, D. S. (Nairobi : Oxford University Press, 1969)
The book examines East Africa with specific reference to: the structure of the economy, the types and determinants of growth, and the centripetal forces that usually compel industries to concentrate in the major towns where they are most likely to reap external economies. D. S. Pearson presents the model of the uneven rate of industrial development. He traces the historical background to the East African Community, and the institutional measures adopted to reduce the national imbalances in economic growth, but do not pretend that these arrangements have resulted in any optimum re-allocation of resources in the industrial sector.
Includes index.
Includes bibliographical references: p. 204-206.
lje 19/02/2018
Loans
Keywords: Industries; Industrial policy